Multimodal Therapeutic Approach in Prolonged Grief Disorder - Sharika Vipin; Jithesh M (AYUSHDHARA, 2025)
Prolonged Grief Disorder (PGD) is characterized by intense, persistent grief that impairs an individual’s ability to function. PGD stands out due to the chronic nature of emotional distress, lasting beyond culturally appropriate mourning periods. If left untreated, PGD can lead to complication such as depression, suicidal thoughts or behaviours, anxiety and sleep disturbances. CBT is the prime choice for management, high dropout rates and longer follow-up make the condition challenging. A multimodal approach including Ayurvedic medicines, yoga, psychotherapies are observed as effective in PGD based on the principles of Unmada chikitsa. Three female patients presented with yearning, preoccupation with the deceased, emotional numbness, and difficulty moving forward with life for more than one and half years. They were diagnosed as PGD as per the DSM V - TR criteria. Ayurvedic management included medicines on a conditional basis along with the same, Jacobson Progressive Muscle Relaxation and yoga was also administered. The assessments were done on 0th day and 21st day with Brief Grief Questionnaire, Hamilton anxiety rating scale and Hamilton depression rating scale. Participants revealed improvement in functional capacity, emotional regulation. Changes noted in both biological and psychological symptoms of grief. There was reduction in the scores of all the scales on assessment. This case series highlights the importance of multimodal approach including Ayurvedic pharmacotherapy in PGD to mitigate the long-term psychological and social impacts of unresolved grief.